Rehabilitation of a child with history of multiple natal teeth and oligodontia in the permanent dentition - Patricia Fernanda Dias; Lizandra Ferrari Guimarães; Ana Lúcia de Souza Freire Sanchez; Laura Guimarães Primo (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2009)
The objective of the present article is to report an uncommon case of a boy with history of 11 natal lost teeth, all belonging to the normal series of primary dentition, associated with absence of up to 21 permanent tooth germs. Such a condition resulted in the necessity for oral rehabilitation. Partial removable prostheses were used as a choice of treatment, and the patient will have to be constantly followed up so that new treatment approaches can be performed according to the patient's development.